Pengembangan Media Pembelajaran Video Avatar Berbasis Artificial Intellegence (AI) bagi Peserta Didik Tingkat Pendidikan Dasar - Azfar, Fani; Sutiah, Sutiah (ISLAMIKA, 2024)
This article reviews the development of artificial intelligence-based avatar video learning media products for elementary-level students. Researchers used the ADDIE R & D model method to develop the media product in its implementation. By the flow of the ADDIE model itself, researchers go through several stages such as analysis, design, development, implementation, and evaluation. This research study shows that the use of products resulting from the development of artificial intelligence-based avatar video media is very suitable for elementary-level students. This is proven by the fact that the product has accommodated the two learning styles, namely auditory and visual so that with the basic nature of students who tend to imagine and are easily interested in concrete things, students become enthusiastic in learning activities.